Adipsin and Leptin as Therapeutic Targets by Dipeptidyl Peptidase-4 Inhibitors in Type 2 Diabetes Mellitus: Review Article - Fathi, Zainab; Mohammad, Jehan (Iraqi Journal of Pharmaceutical Sciences, 2025)
Type 2 diabetes mellitus (T2DM), one of the most common metabolic diseases, is caused by a mix of insulin-sensitive tissues’ inadequate response to insulin and pancreatic β-cells’ impaired insulin secretion. Adipsin is involved in preserving the homeostasis of adipose tissues and enhancing insulin secretion in response to glucose. Adipose tissue secretes adipokines, which are cell-signaling proteins that have been connected to various pathologies as well as a low-grade state of inflammation. Although the regulation of energy homeostasis is a well-established function of the obesity hormone leptin, there is increasing evidence that leptin is also essential for glycaemic control. The hormone leptin is a 167-residue peptide produced by the Lep gene. Adipose tissue is the main source of its secretion. Leptin levels in the blood are undetectable when the Lep gene is functionally inactivated. To increase the precision of disease prediction, offer fresh perspectives on pathophysiology, and aid in the prevention of type 2 diabetes in the future, a validated novel biomarker is necessary. Targeting endogenous proteins has led to the development of several more advanced diagnostic techniques, with adipsin being one of the most promising targets. Therefore, the aim of this review study is to assess the effects of DPP-4 inhibitors on adipsin and leptin in T2DM. The function of DPP-4 (DPP4) inhibitors has changed in recent years. DPP-4 inhibitors do not result in hypoglycemia or weight gain, have a good safety profile, an anti-inflammatory profile, and do not need dose escalation. It can also be used with older diabetic patients and patients with certain forms of chronic kidney disease. Adipsin has the potential to become an early novel biomarker in patients with T2DM.